Apokryphe Schriften Rezeption und Vergessen in der Wissenschaft vom Öffentlichen Recht - Wischmeyer, Thomas; Marsch, Nikolaus; Münkler, Laura (Mohr Siebeck, 2018)
How do concepts and ideas travel within legal academia? Which factors contribute to the success or failure of ideas and individual scholars? The contributions in this volume analyze how the »collective memory« of German public law operates.
PublicationDate: 20190227
Keywords: Wissenschaftstheorie -- Verfassungsrecht -- Rechtstheorie -- Kanon -- Grundlagen -- Rechtsgeschichte -- Verfassungsrecht und Staatslehre -- Verwaltungsrecht -- Völkerrecht -- Array